Left Ventricular Global Function Index: A Potential Predictor of Mortality and Major Adverse Cardiovascular Events in NSTEMI Patients - Mesut Karatas; Cengiz Sabanoglu; Kader Eliz Sahin; Ibrahim Halil Inanc (Medicina)
Background and Objectives: The prognostic value of Left Ventricular Global Function Index (LVGFI) in chronic cardiovascular diseases is well-documented; however, limited evidence exists for its utility in non-ST elevation myocardial infarction (NSTEMI). This study aims to evaluate LVGFI as a predictor of three-year mortality and major adverse cardiovascular events (MACE) in NSTEMI patients. Materials and Methods: This retrospective cohort study included 432 NSTEMI patients divided into tertiles based on LVGFI values: T1 (low), T2 (intermediate), and T3 (high). LVGFI values were derived from echocardiographic imaging. Kaplan–Meier survival analysis was used to assess outcomes, and the Cox proportional hazards models, adjusted for demographics and clinical covariates, determined the association between LVGFI tertiles and three-year outcomes. Results: The average age and sex distribution were similar across tertiles with no significant differences in cardiovascular risk factors or most laboratory parameters. However, significant differences were noted in body surface area (higher in T3), platelet counts (higher in T1), and triglyceride levels (lower in T3). The ROC analysis identified an optimal LVGFI cut-off of 23.22 for predicting three-year mortality, with a sensitivity of 72% and specificity of 75% (AUC: 0.81; 95% CI: 0.74–0.87, p < 0.001). Patients in the T1 exhibited a three-year mortality rate of 25%, compared to 2.1% in the T3. After adjustment, the hazard ratio (HR) for mortality was significantly higher in T1 (HR 11.86; 95% CI: 3.60–39.10) compared to T3. Similarly, MACE rates were highest in T1 (27.1%) and lowest in T3 (7.6%). Conclusions: LVGFI is a significant independent predictor of three-year mortality and MACE in NSTEMI patients.